First aid taking action - National Safety Council (New York McGraw-Hill Higher Education, 2007)
First Aid: Taking Action is a first edition product for McGraw-Hill Higher Education. Part of a series of titles authored by the National Safety Council, First Aid: Taking Action covers the material required for a semester long Advanced First Aid course . The focus is teaching how to recognize and act in any emergency and to sustain life until professional help can arrive. Quality content will feature information based on the 2005 national guidelines for breathing and cardiac emergencies. Other information includes bleeding control, and first aid for sudden illnesses and injuries. Information is presented in a concise easy-to-read manner that works as a handy reference after the course. National Safety Council programs and products are designed to benefit all types of learning styles by combining lectures, video presentations, group discussions, and hands-on training.
Preparing to act -- Acting in an emergency -- The human body -- Assessing the victim -- Basic life support 1: rescue breaths -- Basic life support 2: CPR -- Basic life support 3: choking care -- Basic life support 4: automated external defibrillator (AED) -- Controlling bleeding -- Shock -- Wounds and soft tissue injuries -- Burns -- Head and spinal injuries -- Chest, abdominal, and pelvic injuries -- Bone, joint, and muscle injuries -- Extremity injuries and splinting -- Sudden illness -- Poisoning -- Substance misuse and abuse -- Bites and stings -- Cold and heat emergencies -- Behavioral emergencies -- Pregnancy and childbirth -- Remote location first aid -- Rescuing and moving victims -- Are you prepared? -- Moving forward -- Glossary.
CSSP-6346 donated by The Rotary Club of Beaverton, Oregon, United States of America.
Keywords: First aid in illness and injury; Medical emergencies